METHOD OF APPLICATION FOR A LARGE NUMBER OF BALLS, AS AN EFFECTIVE FACTOR FOR LONG-TERM TRAINING OF HIGHLY QUALIFIED TABLE TENNIS ATHLETES - MOCROUSOV E.; GROSUL V. (Editura Universitatii Transilvania din Brasov, 2019)
The modern system of training table tennis players is a complex, multifactorial process, including goals, objectives, means, methods, organizational forms, material and technical conditions, etc. During the last years, along with the use of traditional methods in table tennis, the method of working with a large number of balls has become widespread. The object of research is the theory and methodology of long-term training for table tennis, based on the use of a large number of balls. The purpose of the research is to improve the methodology of long-term training for table tennis based on the use of a large number of balls.